Michigan: An Intrusive Inquiry into EPA’s Rulemaking Process - Packard, Lauren (Columbia Journal of Environmental Law, 2019)
In 2015, the Supreme Court decided Michigan v. EPA, finding that the U.S. Environmental Protection Agency (“EPA”) interpreted section 112 of the Clean Air Act unreasonably when it decided to regulate toxic mercury emissions from power plants without first considering compliance costs. Justice Scalia, writing for a 5-4 majority, found that the term “appropriate and necessary” in section 112 “naturally and traditionally” includes a consideration of costs. Consequently, the Court found that EPA’s decision to regulate mercury emissions did not warrant deference under Chevron v. Natural Resources Defense Council because EPA did not predicate its determination on an analysis of compliance costs. Rather, EPA decided to regulate emissions from power plants because such emissions pose a public health hazard, pre-existing regulations did not adequately address this hazard, and control technologies exist to mitigate it. In her dissent, Justice Kagan pointed out that the agency had considered costs at the implementation stage of the rulemaking process and criticized the majority for its “micromanagement” of EPA’s rulemaking process. This Note will argue that Michigan reflects, for the first time, a presumption in favor of cost considerations by the Court. Michigan also represents the first instance where the Court has not only decided whether an agency should consider costs and how formal or informal these considerations may be, but has ruled on when in the rulemaking process these considerations must take place. Further, Michigan indicates a trend toward a more searching application of Chevron deference. Consequently, in order to withstand judicial review post-Michigan, cautious agencies—and EPA in particular—should alter their rulemaking practices to include cost considerations when making threshold determinations to regulate. Although cost considerations do not require cost-benefit balancing per se, agencies should consider framing considerations as such because Justice Scalia’s reasoning in Michigan implicitly requires such analysis.